NILAI KEARIFAN LOKAL DALAM CERITA PANJI LARAS-LIRIS DI KABUPATEN LAMONGAN - Maulani, Rif'atul; Budiyono, Sunu Catur Budiyono (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the value of local wisdom in the Panji Laras-Liris Story in Lamongan Regency. This research uses a qualitative descriptive approach with literary sociology theory. The data is in the form of quotations contained in the book Panji Laras-Liris Story. The data source comes from the book Panji Laras-Liris Story in Lamongan Public Library. Data were collected through reading and note-taking techniques. The data analysis used Miles and Huberman's interactive model consisting of data reduction, data presentation, and conclusion drawing/verification. The results showed that there were five forms with seven data points of local wisdom values as follows: First, religious value, namely the value of spreading goodness. Second, moral value, namely the value of keeping speech and the value of keeping promises. Third, social value, namely the value of gotong royong. Fourth, the value of tolerance, which is the value of respect without discrimination. Fifth, the value of integrity, namely the value of being keen to seek knowledge and the value of not giving up